1987
DOI: 10.1042/cs0730117
|View full text |Cite
|
Sign up to set email alerts
|

The influence of oral alkali citrate on intestinal calcium absorption in healthy man

Abstract: The influence of citrate on intestinal calcium absorption (CaA) was studied in eight healthy males. On separate occasions, either a load containing 5 mmol of calcium chloride and 21 mmol of citrate in the form of sodium potassium citrate or a citrate-free vehicle load corrected for pH and cations was ingested. CaA was measured over 3 h with a 47Ca-85Sr double tracer method. After citrate administration, 10 min fractional CaA decreased significantly from 30 to 110 min post-load, and 3 h cumulative CaA dropped t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…However, unlike strontium, barium, and radium, the other alkaline earth elements, calcium is an essential element and physiological mechanisms facilitate its intestinal absorption. (226) Calcium absorption has been measured in numerous volunteer studies, and the reported mean absorption values were in the range 0.2–0.5 in most cases (Samachson, 1963; DeGrazia and Rich, 1964; Lutwak, 1969; Mautalen et al., 1969; Jovanovic, 1978; Cochet et al., 1983; Marchandise et al., 1986; Spencer et al., 1987; Harvey et al., 1988; Heaney et al., 1989, 1999). Greater mean values of 0.6 (Sambrook et al., 1985) and 0.7 (Rumenapf and Schwille, 1987) have also been reported for normal volunteers. These differences may probably be explained by the large interindividual differences in calcium absorption observed in healthy subjects, with individual values ranging from 0.3 to 0.6 (Barger-Lux and Heaney, 1995) or even from 0.4 to 0.9 (Isaksson et al., 2000).…”
Section: Calcium (Z = 20)mentioning
confidence: 76%
See 1 more Smart Citation
“…However, unlike strontium, barium, and radium, the other alkaline earth elements, calcium is an essential element and physiological mechanisms facilitate its intestinal absorption. (226) Calcium absorption has been measured in numerous volunteer studies, and the reported mean absorption values were in the range 0.2–0.5 in most cases (Samachson, 1963; DeGrazia and Rich, 1964; Lutwak, 1969; Mautalen et al., 1969; Jovanovic, 1978; Cochet et al., 1983; Marchandise et al., 1986; Spencer et al., 1987; Harvey et al., 1988; Heaney et al., 1989, 1999). Greater mean values of 0.6 (Sambrook et al., 1985) and 0.7 (Rumenapf and Schwille, 1987) have also been reported for normal volunteers. These differences may probably be explained by the large interindividual differences in calcium absorption observed in healthy subjects, with individual values ranging from 0.3 to 0.6 (Barger-Lux and Heaney, 1995) or even from 0.4 to 0.9 (Isaksson et al., 2000).…”
Section: Calcium (Z = 20)mentioning
confidence: 76%
“…These differences may probably be explained by the large interindividual differences in calcium absorption observed in healthy subjects, with individual values ranging from 0.3 to 0.6 (Barger-Lux and Heaney, 1995) or even from 0.4 to 0.9 (Isaksson et al., 2000). Indeed, calcium absorption depends first on the intraluminal concentration of ionised calcium (Schachter et al., 1960), which can be reduced locally by the presence of calcium binding agents such as EDTA or citrate ions (Rumenapf and Schwille, 1987). Additional variability may be associated with morphological factors as calcium absorption is positively correlated with body size (Davies et al., 2000; Barger-Lux and Heaney, 2005) and many nutritional factors.…”
Section: Calcium (Z = 20)mentioning
confidence: 99%
“…Another hypocalciuric effect of magnesium citrate may be attributable to the observation that citrate combines with dietary calcium in the intestine to form the nondissociating, readily dissolving, and poorly absorbable calcium-citrate chelate complex [ 17,18]:…”
Section: Discussionmentioning
confidence: 99%
“…Other studies, however, have not found suppression of 1,25(OH) 2 D 3 production in normal adults [25], nor a reduction in the intestinal absorption of calcium or phosphorus after the induction of metabolic acidosis [26]. There are reports of either increased [27,28] or decreased [29] intestinal calcium absorption after alkali administration.…”
Section: Gastrointestinal Calcium Handling In Metabolic Acidosismentioning
confidence: 95%